Verdict assessing the civil jury system - Litan, Robert E., 1950- (Brookings Institution, 1993)
The right to a jury trial is a fundamental feature of the American justice system. In recent years, however, aspects of the civil jury system have increasingly come under attack. Many question the ability of lay jurors to decide complex scientific and technical questions that often arise in civil suits. Others debate the high and rising costs of litigation, the staggering delay in resolving disputes, and the quality of justice. Federal and state courts, crowded with growing numbers of criminal cases, complain about handling difficult civil matters. As a result, the jury trial is effectively be.